ADHD symptoms in non-treatment seeking young adults: relationship with other forms of impulsivity. (29th September 2016) - Chamberlain, Samuel R.; Ioannidis, Konstantinos; Leppink, Eric W.; Niaz, Faiza; Redden, Sarah A.; Grant, Jon E.
Abstract : Objective: Attention-deficit hyperactivity disorder (ADHD) has been associated with various manifestations of impulsivity in adults, including elevated rates of other impulsive disorders, substance use, questionnaire-based impulsivity scores, and inhibitory dysregulation on neurocognitive tests. The relationship between ADHD and all these other forms of impulsivity has yet to be explored within the context of a single comprehensive study. Methods: A total of 423 young adults, who gambled ≥5 times in the preceding year, were recruited using media advertisements and undertook detailed assessment including structured psychiatric interview, questionnaires, and neurocognitive tests. Participants with ADHD symptoms were identified using the Adult ADHD Self-Report Scale Screener (ASRS-V1.1) and were compared to controls using multivariate analysis of variance (MANOVA). Results: ADHD symptoms were found in 20.3% of the sample, but only 7.3% of these subjects had ever received a formal diagnosis. ADHD symptoms were associated with significantly lower quality of life, lower self-esteem, higher emotional dysregulation, higher impulsivity questionnaire scores, more problematic Internet use, greater occurrence of psychiatric disorders, and impaired stop-signal reaction times. Of these variables, stop-signal reaction times and Barratt attentional impulsiveness were the strongest predictors of group classification. Conclusions: ADHD symptoms are common and under-diagnosed in young adults who gamble, and are most strongly linked with certain other types of impulsivity (questionnaire- and cognitive-based measures) and with emotional dysregulation, suggesting that these are each important considerations in understanding the pathophysiology of the disorder, but also potential treatment targets. It is necessary to question whether treatment for adult ADHD could be enhanced by considering self-esteem, emotional reactivity, and impaired inhibitory control as specific treatment targets, in addition to the core diagnostic symptoms of the disorder.